2020
DOI: 10.2174/1570159x18666200203101828
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Alzheimer’s Association with Related Proteins: Pathological Role and Therapeutic Significance

Abstract: : Alzheimer’s is an insidious, progressive, chronic neurodegenerative disease which causes the devastation of neurons. Alzheimer's possess complex pathologies of heterogeneous nature counting proteins as one major factor along with enzymes and mutated genes. Proteins such as amyloid precursor protein (APP), apolipoprotein E (ApoE), presenilin, mortalin, calbindin-D28K, c-reactive protein, heat shock proteins (HSPs), and prion protein are some of chief elements in the foremost hypotheses of AD like amyloid-beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 196 publications
0
11
0
Order By: Relevance
“…3 Among numerous brain diseases, Alzheimer's disease (AD), anxiety and depression are reported to predominantly affecting individuals and their families. 4 Alzheimer's disease (AD) is a prevailing illness presenting memory loss in elder individuals that has affected 24 million populace worldwide. 5 The disease encompasses an initial decline in cognition that gradually influences all intellectual functions resulting in an individual's dependency on others for basic daily activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Among numerous brain diseases, Alzheimer's disease (AD), anxiety and depression are reported to predominantly affecting individuals and their families. 4 Alzheimer's disease (AD) is a prevailing illness presenting memory loss in elder individuals that has affected 24 million populace worldwide. 5 The disease encompasses an initial decline in cognition that gradually influences all intellectual functions resulting in an individual's dependency on others for basic daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among numerous brain diseases, Alzheimer’s disease (AD), anxiety and depression are reported to predominantly affecting individuals and their families. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Aβ is produced by the cleavage of APP by βand γ-secretase [29]. Previous studies have found that the overexpression of APP led to the increase of Aβ, which is closely related to the occurrence of AD [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. It has been shown that BHBA can improve cognitive behavior in an Alzheimer's disease mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some studies show that in aging, the neuronal repair processes and the expression of growth factors that promote neurogenesis decrease (Dahan et al., 2020). Therefore, aging is a crucial factor in several neurodegenerative disorders such as Alzheimer’s and Parkinson’s diseases (Kandlur et al., 2020; Kumar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%